Imperiets genfærd – Profeterne i Evighedsfjorden og den dansk-grønlandske historieskrivning - Thisted, Kirsten (Nordlit, 2015)
While the official Denmark has declined taking part in a reconciliation process with Greenland, its former colony, a large literary audience has embraced the novelist Kim Leine, who puts colonial history and Danish-Greenlandic power relations on the agenda. Originally published in 2012, his novel Profeterne i Evighedsfjorden (English title: The Prophets of Eternal Fjord) has received huge attention and several prestigious literary awards, but it has also been the target of criticism for painting a distorted picture of Denmark’s conduct in Greenland. The article examines how the novel relates to the established narratives about Danish colonialism and how it contributes to the ongoing negotiations. The novel’s use of narrative modes is analysed in light of the assumption that certain modes are associated with certain plots, where a particular framing of the past defines a space of possibility for the way we shape the future. It is argued that the novel draws on the anticolonial dream of ‘total revolution’ and supports the struggle of the colonised to break free from the colonial power and establish their own nation state. Its key narrative mode, however, is not the preferred mode in anticolonialist literature, heroic romance; instead it is tragedy. The novel portrays the profound transformation of society and subjectivity that is brought about by modernity with Christianity and colonialism as its vehicle. As a consequence of this transformation, resistance cannot be posited from a point outside modernity but arises from within modernity itself. Thus the protagonists of the novel are not only portrayed as equals but as actors in the same universe, regardless of the highly asymmetrical power relations between Danes and Greenlanders. In this sense, the book participates in efforts to reframe the Danish-Greenlandic relationship based on the new language of equality and partnership found in the Act on Greenland Self-Government.